Assessing a brain-computer interface by evoking the auditory cortex through binaural beat - Potgieter, Louwrens (University of the Free State, 2013)
English: Why can some people study, read books, and work while listening to music or with noise in the background while other people simply cannot? This was the question that prompted this research study. The aim of this project was to assess the impact of binaural beats on participants during the performance of a task. The participants were exposed to different binaural beats that changed the dominant brainwaves while they were engaging in the task. A braincomputer interface was used to monitor the performance of the task in which a Lego Mindstorm robot was controlled as it moved through a course. To accomplish the aim of the project, the effects of binaural tones on participants’ task performance were investigated in relation to participants’ levels of frustration, excitement, engagement, meditation and performance. Participants were monitored by means of using an Emotiv EPOC neuroheadset. Although previous studies on binaural beats have been done, most of these studies were done on Attention deficit-hyperactivity disorder (ADHD) children, with users performing everyday tasks. In these studies, time was the only metric used. The researcher collected data by means of questionnaires that were completed by the participants to obtain personal information and measure the user experience. The aspects of frustration, excitement, engagement, meditation and performance were determined using the Emotiv headset in combination with the Emotiv software development kit, Microsoft Robotics Studio and software created by the researcher. After intensive statistical analysis, the researcher found that different sound frequencies did indeed affect user performance. Sessions where no sound frequency was applied were associated with more errors and longer time durations compared with all other frequencies. It can be concluded that invoking a participant’s dominant brainwave by means of binaural tones can change his/her state of mind. This in turn can affect the long-term excitement, short-term excitement, engagement, meditation, frustration or performance of a participant while performing a task. Much remains to be learned, in particular regarding the combination of brain-computer interfaces and human-computer interaction. The possibility of new cutting-edge technologies that could provide a platform for further in-depth research is an exciting prospect.

Afrikaans: Waarom kan sommige mense studeer, boek lees, of werk terwyl hulle na musiek luister of geraas in die agtergrond het, terwyl ander stilte nodig het terwyl hulle sulke take doen? Die doel van hierdie navorsingstudie was om hierdie verskynsel te ondersoek. Die doel van hierdie projek was om die impak van binaurale ritmes op die gebruikers, tydens die uitvoering van 'n taak, te assesseer. Die gebruikers is aan verskillende binaurale ritmes blootgestel wat die dominante breingolwe verander terwyl hulle betrokke was by die taak. 'n Brein-rekenaar-koppelvlak is gebruik om die uitvoer van 'n taak te monitor: die taak was om ’n Lego Mindstorm robot deur ‘n baan te laat beweeg. Om die doel van die projek te bereik is die effek van binaurale ritmes op deelnemers se taakprestasie ondersoek met betrekking tot die deelnemers se vlakke van frustrasie, opwinding, betrokkenheid, meditasie en prestasie. Deelnemers is gemonitor deur middel van 'n Emotiv EPOC neuro-kopstuk. Hoewel vorige studies op binaurale ritmes gedoen is, is die meeste daarvan op kinders met aandag tekort hiperaktiwiteit versteuring (ADHD) gedoen, terwyl die gebruikers alledaagse take uitgevoer het. Tyd was die enigste maatstaaf wat gebruik was in hierdie studies. Vraelyste is deur die gebruikers voltooi om data te versamel. Persoonlike inligting is verkry en die gebruiker se ervaringsvlakke is gemeet. Die vlakke van frustrasie, opwinding, betrokkenheid, meditasie en prestasie is bepaal deur gebruik te maak van ‘n kombinasie van die Emotiv kopstuk, die Emotiv sagteware-ontwikkeling pakket, Microsoft Robotics Studio en sagteware geskep deur die navorser. Na intensiewe statistiese analise het die navorser gevind dat verskillende klankfrekwensies wel gebruikerprestasie beïnvloed. Sessies waar geen frekwensie toegepas is nie het groter getalle foute opgelewer, en hierdie sessies het ook langer geneem om uit te voer in vergelyking met sessies waarin frekwensies wel toegepas is. Daar kan afgelei word dat die verandering van 'n gebruiker se dominante breingolf deur middel van binaurale ritmes wel die bewussynstaat van die gebruiker kan verander. Dit kan dan die langtermyn-opwinding, korttermyn-opwinding, betrokkenheid, meditasie, frustrasie of prestasie van 'n gebruiker beïnvloed, terwyl hy/sy die taak uitvoer. Daar is baie wat nog geleer moet word, in besonder met betrekking tot die kombinasie van brein-rekenaar koppelvlakke en mens-rekenaar-interaksie. Die moontlikheid van nuwe baanbrekertegnologie wat 'n platvorm kan voorsien vir verdere in-diepte navorsing is 'n opwindende vooruitsig.
Keywords: Dissertation (M.Sc. (Computer Science and Informatics))--University of the Free State, 2013; Brain-computer interfaces; Computational neuroscience; Neural networks -- Computer science